Gaining a deeper understanding of the meaning of the carelessness parameter in the 4PL IRT model and strategies for estimating it - Pardede, Timbul; Santoso, Agus; Diki, Diki; Retnawati, Heri; Rafi, Ibnu; Apino, Ezi; Rosyada, Munaya Nikma (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
Three popular models are used to describe the characteristics of the test items and estimate the ability of examinees under the dichotomous IRT model, namely the one-, two-, and three-parameter logistic models. The three-item parameters are discriminating power, difficulty, and pseudo-guessing. In the development of the dichotomous IRT model, carelessness or upper asymptote parameter was proposed, which forms a four-parameter logistic (4PL) model to accommodate a condition where a high-ability examinee gives an incorrect response to a test item when he/she should be able to respond to the test item correctly. However, the carelessness parameter and the 4PL model have not been widely accepted and used due to several factors, and people's understanding of that parameter and strategies for estimating it is still inadequate. Therefore, this study aims to shed light on ideas underlying the 4PL model, the meaning of the carelessness parameter, and strategies used to estimate that parameter based on the extant literature. The focus of this study was then extended to demonstrating practical examples of estimating item and person parameters using the 4PL model using empirical data on responses of 1,000 students from the Indonesia Open University (Universitas Terbuka) on 21 of 30 multiple-choice items on the Business English test, a paper-and-pencil test. We mainly analyzed empirical data using the